An analysis on the legislation for disabled people: descriptive-exploratory study - Baptista, Rosilene Santos; Vieira, Neiva Francenely Cunha; Ximenes, Lorena Barbosa; Pagliuca, Lorita Marlena Freitag (Online Brazilian Journal of Nursing, 2010)
This paper consists of an analysis on legislation that defines public policy for disabled people. The paper aims to discuss health promotion, based on the Ottawa Charter for health promotion. We used legislation from 80’s, 90’s and 00’s which was obtained from the Ministry of Health website and the operation manual for disabled people. The selected documents were submitted to exploratory reading seeking for the presence or absence of the pillars of health promotion: the strengthening of community action, development of personal skills and reorientation of health services. As a conclusion, we may infer that it is very difficult to reasoning on health promotion versus public policy, when taken into account compliance to autonomy, empowerment and social inclusion. Lastly, it follows from this paradigm, the necessity of nurses, other health professionals and society to avoid prejudice against the inclusion of disabled people.